Perfluorooctane Sulfonate Exposure Induces Cardiovascular Dysfunction in Female Rats: Role of Ovaries - Porfirio, Karina; Yadav, Pankaj; Dangudubiyyam, Sri Vidya; Hofmann, Alissa; Mishra, Jay S.; Kumar, Sathish (Cardiology and Cardiovascular Medicine, 2024)
Per-and polyfluoroalkyl substances (PFAS) are pervasive environmental pollutants frequently detected in drinking water worldwide. Reports linking PFAS exposure to cardiovascular disease have increased significantly in recent years. Furthermore, women appear to be more susceptible to the adverse effects of PFAS. However, the potential role of ovaries in the increased vulnerability of females to PFAS-related health effects remains unknown. In this study, we investigated the impact of perfluorooctane sulfonate (PFOS), a prominent PFAS, on the cardiovascular function in female rats with intact ovaries and ovariectomized (OVX) females. Bilateral OVX or sham surgeries were performed in 8-week-old female SD rats. Following recovery from surgeries, the rats were given drinking water containing 50 μg/mL of PFOS for 3 weeks. Control groups received PFOS-free water. PFOS exposure significantly reduced body weight but increased blood pressure similarly in both intact and OVX rats. Echocardiography analysis revealed that PFOS exposure decreased cardiac output, end-systolic volume, and end diastolic volume in intact but not OVX rats. Vascular function studies demonstrated that PFOS equally reduced endothelium-dependent and -independent relaxation responses in intact and OVX rats. The endothelium-independent contractile responses were more pronounced in both intact and OVX rats. eNOS protein levels were similarly decreased in both intact and OVX rats. In conclusion, PFOS affects cardiac function through hormone-dependent mechanisms, while vascular function is impaired independent of ovarian status, indicating an intricate interplay between PFOS exposure, ovarian status, and cardiovascular function.